2010
DOI: 10.1080/00224540903366388
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Entitativity and the Black-Sheep Effect: When Will We Denigrate Negative Ingroup Members?

Abstract: Although ingroup favoritism is a robust effect, there are notable exceptions. For example, the outgroup extremity effect indicates outgroup derogation, whereas the black-sheep effect indicates ingroup derogation. We propose that perceived entitativity, the degree to which a group is viewed as a unified social entity, may help explain ingroup derogation. Negative ingroup members from high perceived entitativity groups may pose a meaningful threat to the perceiver's social identity that can be alleviated by deni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 30 publications
1
45
0
Order By: Relevance
“…For instance, ‘ingroup homogeneity’, a main factor of ingroup identification (Leach et al ., ), might be especially relevant to black sheep reactions against deviant ingroup members. Prior research, for example, has indicated that perceived entitativity (i.e., the degree to which a group appears to be a unified social entity) which is tightly related to the concept of ingroup homogeneity (Hamilton, Sherman, & Rodgers, ) may help explain ingroup derogation (Lewis & Sherman, ; Yzerbyt, Castano, Leyens, & Paladino, ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ‘ingroup homogeneity’, a main factor of ingroup identification (Leach et al ., ), might be especially relevant to black sheep reactions against deviant ingroup members. Prior research, for example, has indicated that perceived entitativity (i.e., the degree to which a group appears to be a unified social entity) which is tightly related to the concept of ingroup homogeneity (Hamilton, Sherman, & Rodgers, ) may help explain ingroup derogation (Lewis & Sherman, ; Yzerbyt, Castano, Leyens, & Paladino, ).…”
Section: Discussionmentioning
confidence: 99%
“…The BSE (see Marques & Paez, 1994, for a review) was replicated in various intergroup contexts with a broad range of dependent variables (e.g., Bègue, 2001;Chekroun & Nugier, 2005;DeCremer & Vanbeselaere, 1999;Marques et al, 2001;Matthews & Dietz-Uhler, 1998;Oishi & Yoshida, 2002), and supported the social identity perspective on the BSE (for a review, see Marques & Paez, 1994). It is moderated by ingroup identification (Branscombe, Wann, Noel, & Coleman, 1993) and other group-based factors such as group members' status (Pinto et al, 2010), accountability (Abrams, Rutland, Cameron, & Ferrell, 2007), or perceived entitativity of the ingroup (Lewis & Sherman, 2010). Additional research suggested that the BSE may also result from an ingroup member's personal distancing from the norm deviant (Eidelman & Biernat, 2003), or the violation of expected behavior (Biernat, Vescio, & Billings, 1999).…”
Section: Responses To Intergroup Norm Deviancementioning
confidence: 93%
“…In support, a number of studies across a variety of contexts reveal that majority/non-stigmatized group members show no in-group bias whereas minority/stigmatized group members show an in-group favorability bias (e.g., Knobloch-Westerwick, Appiah, & Alter, 2008). These findings are not surprising given in-group preference and out-group discrimination are more likely to occur when people highly identify with their in-group and the in-group holds significant importance in defining their self-concept (Lewis & Sherman, 2010;Vanhoomissen & Van Overwalle, 2010).…”
Section: Social Identity Theory and In-group Preferencementioning
confidence: 71%
“…This is to say that two people may be members of numerous groups but their memberships to only a few groups hold any significance. The more identification and pride people hold for their in-group the more likely they will express in-group favoritism (Lewis & Sherman, 2010) and negative feelings toward relevant out-groups (Vanhoomissen & Van Overwalle, 2010).…”
Section: Social Identity Theory and In-group Preferencementioning
confidence: 99%
See 1 more Smart Citation